2016
DOI: 10.18632/oncotarget.11744
|View full text |Cite
|
Sign up to set email alerts
|

HLA-E expression and its clinical relevance in human renal cell carcinoma

Abstract: The non-classical human leukocyte antigen E (HLA-E) expression is frequently overexpressed in tumor diseases, transplants and virus-infected cells and represents an immunomodulatory molecule by binding to the receptors CD94/NKG2A, -B and –C on NK and T cells. Due to its immune suppressive features HLA-E expression might represent an important mechanism of tumors to escape immune surveillance.While an aberrant expression of the non-classical HLA-G antigen in human renal cell carcinoma (RCC) has been demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…We and others reported a negative correlation of HLA-E on the overall survival of cancer patients (Talebian Yazdi et al, 2016, Gooden et al, 2011, van Esch et al, 2014, Seliger et al, 2016, Andersson et al, 2016, Silva et al, 2011); in particular, the beneficial effect of high CD8 T cell counts within tumor was mitigated by high protein expression of HLA-E (Talebian Yazdi et al, 2016, Gooden et al, 2011). These findings suggested that NKG2A receptor expression on tumor-infiltrating lymphocytes might hamper their function by interaction with HLA-E in the microenvironment.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…We and others reported a negative correlation of HLA-E on the overall survival of cancer patients (Talebian Yazdi et al, 2016, Gooden et al, 2011, van Esch et al, 2014, Seliger et al, 2016, Andersson et al, 2016, Silva et al, 2011); in particular, the beneficial effect of high CD8 T cell counts within tumor was mitigated by high protein expression of HLA-E (Talebian Yazdi et al, 2016, Gooden et al, 2011). These findings suggested that NKG2A receptor expression on tumor-infiltrating lymphocytes might hamper their function by interaction with HLA-E in the microenvironment.…”
Section: Introductionmentioning
confidence: 65%
“…HLA-E is ubiquitously expressed at low levels, but very high expression can be found on trophoblasts and ductal epithelial cells in immune-privileged tissues like placenta and testis, respectively. In cancers, HLA-E is frequently overexpressed compared to their non-transformed counterparts, including melanoma and carcinomas of lung, cervix, ovarium, vulva and head/neck (Talebian Yazdi et al, 2016, Gooden et al, 2011, van Esch et al, 2014, Seliger et al, 2016, Andersson et al, 2016, Silva et al, 2011). The physiological function of HLA-E is to present ‘self’ peptides derived from other HLA class I molecules (DeCloux et al, 1997, Kraft et al, 2000, O’Callaghan et al, 1998) and to limit autoimmune reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…51 In contrast, complexes composed of HLA-E and Prdx5 did not interact with NKG2A and therefore did not downregulate NK cell function. 51 HLA-E might be upregulated in response to cytokines like IFNg 52 suggesting that an upregulation of HLA-E in response to MSA cannot be excluded. Thus, further analyses are required to determine the impact of MSA treatment on the expression of MHC class Ib molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Once the best condition for the combined administration of anti-CTLA4 antibodies and the oncolytic virus was identified in a mouse model of RCC, it was shown that the synergistic effects of the combined therapy required the participation of CD8+ T cells, NK cells, and IFNγ for the anti-tumor response [182]. Interestingly, HLA-E expression has been reported in RCC tumors [183,184]. However, whether the use of anti-NKG2A Abs could benefit RCC patients remains unexplored.…”
Section: Nk Cells and Renal Cell Carcinomamentioning
confidence: 99%